Numerical Computations of Transonic Critical Aerodynamic Behavior of a Realistic Artillery Projectile - M. Kridi, Ahmed F. (Al-Khwarizmi Engineering Journal, 2009)
The determination of aerodynamic coefficients by shell designers is a critical step in the development of any projectile design. Of particular interest is the determination of the aerodynamic coefficients at transonic speeds. It is in this speed regime that the critical aerodynamic behavior occurs and a rapid change in the aerodynamic coefficients is observed. Two-dimensional, transonic, flow field computations over projectiles have been made using Euler equations which were used for solution with no special treatment required. In this work a solution algorithm is based on finite difference MacCormack’s technique for solving mixed subsonic-supersonic flow problem. Details of the asymmetrically located shock waves on the projectiles have been determined. Computed surface pressures have been compared with experimental data and are found to be in good agreement. The pitching moment coefficient, determined from the computed flow fields, shows the critical aerodynamic behavior observed in free flights.